Perkembangan dan Pemilihan Karier Menurut Ginzberg dan Implikasinya Terhadap Bimbingan dan Konseling - Juliana Batubara (Jurnal Konseling dan Pendidikan, 2013)
The concept of career development and selection by Ginzberg grouped into fourt elements: process, irreversibilitas, compromise and optimization. As for the career selection process occurs through three periods, namely the period starting fantasy childhood up to 11 years. Tentative period (early adolescence) at the age of 11 to 17 years, which consists of several stages, interests, capacities, values and transitions. Realistic period (mid-teens) at the age of 17 years to early adulthood, approximately 24 years old. This period consists of several stages, namely the exploration phase, and the phase crystallization and specification stage. The power of this theory is that an individual can gradually make the choice to get a career position. The weakness lies in the individual's relationship to the phasepassed.